(untitled) (Fiep Bulletin - online, 2013)
This research is to study the object of the game as a teaching resource and to analyze how this type of activity is being designed and addressed by teachers who work in Child Rearing and the initial grades of elementary school and, even, for students of the Course of Pedagogy Faculty of Science and Technology - UNESP, Campus of Presidente Prudente, Sao Paulo, Brazil. The central goal of the research was to understand whether the process of initial and continuous training are ensuring the subjects studied a solid theoretical basis that allows the use of the game through teaching in the context of education for children. To this end, adopted as a qualitative research methodology and procedures were used as: the deepening bibliographic questionnaires and semi-structured, implemented with the research subjects, seeking to understand concepts related categories: conceptualization, development and importance of the game in the school. As the results were raised representations of teachers and learners on the categories and found superficial and eclectic visions that appear in concepts and practices of teachers, in the process of training or even with extensive experience teaching. It was found that the processes of training, therefore, are not able to offer a solid theoretical support that can smoth down employment of the game in the school. It proposes that a process of training that incorporates the categories: conceptualization, development and importance of the game is a possible path to be exploited, because it allows a broader view of the phenomenon and at the same time, enables the construction of specific media theorists who meets conceptions of education that include children in their uniqueness and needs.